Penerapan Dinamika Kelompok Sosial Dalam Meningkatkan Perkembangan Anak Usia Toddler Di Posyandu Kelurahan Lirboyo Kediri. - Erna Susilowati; Elfi Quyumi Rahmawati (Akademi Keperawatan Dharma Husada Kediri, 2017)
A healthy child will show optimal growth if given an adequate bio-physic and psychosocial environment. Each parent wishes that her child can grow optimally with growth that achieves the best growth and development according to the genetic potential that is present in the child and this must be fulfilled from an early age. The purpose of this study is to determine the effect of social group dynamics in improving the development of toddler age children. This research is a pre experimental research with one group pre-post test design approach on toddler age population in Lirboyo Kediri village. Subjects were taken by random sampling of 50 children. Child development data was obtained by DDST (Denver Devalopment Screning Test) measurement. Data analysis using bivariate analysis is Wilcoxon different test with significance level α = 0.05. The result of this research is the influence of social group dynamics with personal social development (p 0,000). There is influence of social group dynamics with fine motor development (p 0.003), There is influence of social group dynamics on language development (p 0,000) gross motor development (p 0.003) with early detection of growth of Todler-age children is expected to delay the development of children can be prevented.